Hematological parameters and associated factors among adult patients with type 2 diabetes mellitus attending selected hospitals in Garowe, Puntland, Somalia: A comparative cross-sectional study - Mohamud Abshir Musse; Haftu Asmerom; Mesay Arkew; Rajesh Sarkar; Winner Kucha (PLoS ONE, 2026)
Background Diabetes mellitus is characterized by elevated blood glucose levels resulting from inadequate insulin production or ineffective insulin utilization. Type 2 diabetes, the most prevalent form, is associated with alterations in hematological parameters. Notably, there is no evidence addressing hematological parameters and their associated factors among adult patients with type 2 diabetes mellitus in Garowe City. Thus, this study aimed to assess hematological parameters and associated factors among adult patients with type 2 diabetes mellitus in comparison to healthy controls attending hospitals in Garowe, Puntland, Somalia, from October 1 to November 15, 2024. Method A comparative cross-sectional study was conducted 266 participants (133 type 2 diabetic patients and 133 comparative groups) using a systematic random sampling technique. Data were collected using questionnaires, checklists, and laboratory tests. Hematological parameters, fasting blood glucose, and glycated hemoglobin were measured. The collected data were entered into Epi-data v3.1, and exported to STATA v17 for analysis. Independent t-test, Mann-Whitney U-test, and correlation were used. A multivariable logistic regression model was used to see associations between predictors and outcomes. A p -value < 0.05 was considered statistically significant. Results The current study found that the absolute counts of neutrophil, mean corpuscular volume, mean corpuscular hemoglobin concentration, mean platelet volume, and platelet distribution width were significantly different between type 2 diabetic patients and the comparative group ( p < 0.05). Furthermore, the most prevalent hematological abnormalities among type 2 diabetic patients were anemia (31.6%), monocytosis (23.3%), thrombocytopenia (7.5%), and leukocytosis (6.8%). Multivariable analysis indicated that poor glycemic control was significantly associated with anemia (AOR = 3.06, 95% CI: 1.06–8.8), while systolic blood pressure > 140 mmHg was significantly associated with leukocytosis (AOR = 6.09, 95% CI: 1.09–33.9) in type 2 diabetic patients. Conclusions Absolute neutrophil count, mean corpuscular volume, mean corpuscular hemoglobin concentration, mean platelet volume, and platelet distribution width differed significantly between type 2 diabetes mellitus patients and the comparative group. Anemia, monocytosis, thrombocytopenia, and leukocytosis were the most frequently observed hematological abnormalities in both groups. Poor glycemic control was significantly associated with anemia, while elevated systolic blood pressure was associated with leukocytosis among type 2 diabetes mellitus patients. The occurrence of anemia in both groups suggests that factors beyond diabetes may contribute to its burden in this population.